2019
DOI: 10.1007/s00405-019-05317-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of tinnitus in Polish otosclerosis patients qualified for stapes surgery

Abstract: Purpose To assess the prevalence and severity of tinnitus among a group of Polish patients with otosclerosis who qualified for stapes surgery. A secondary objective was to gauge the relationship between tinnitus severity and hearing thresholds. Methods Based on the eligibility criteria, 460 adults with otosclerosis (236 women, 134 men) were included in the study. The Tinnitus Functional Index (TFI) was used to assess tinnitus severity. Hearing thresholds for air and bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…There was a significant positive correlation between TFI grading and pure tone average as well as the tinnitus loudness match above hearing thresholds of the subjects. The findings of Dziendzie et al [26] also showed a positive correlation between TFI scores and the mean air conduction levels. The significant association of TFI score with TLM reported in our study may submit that a rise in tinnitus loudness might result into a worsened effect on the QoL of tinnitus patient.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…There was a significant positive correlation between TFI grading and pure tone average as well as the tinnitus loudness match above hearing thresholds of the subjects. The findings of Dziendzie et al [26] also showed a positive correlation between TFI scores and the mean air conduction levels. The significant association of TFI score with TLM reported in our study may submit that a rise in tinnitus loudness might result into a worsened effect on the QoL of tinnitus patient.…”
Section: Discussionmentioning
confidence: 73%
“…This study included all consenting adults of age 18 years and above who presented to Ear, Nose and Throat (ENT) clinic with tinnitus symptom (as primary complaint) with or without associated hearing loss. Tinnitus was clinically diagnosed to be significant when it occurred for at least once a week and lasted for at least 5 minutes [26]. The duration of tinnitus was also classified into acute (< 3 months), subacute (3 months to less than 6months) and chronic (≥ 6 months) tinnitus according to the Tinnitus Clinical Practice Guideline [19] and the Multidisciplinary European Guideline for management of tinnitus [20].…”
Section: Methodsmentioning
confidence: 99%
“…4 Similar to the statistically significant association between the degree of hearing loss and TFI grading, Dziendzie et al found a positive correlation between the total TFI scores and average air conduction thresholds. 41 With an increase in hearing threshold, a larger tinnitus severity was observed. 41 The association between degree of hearing loss and the TFI grading found a statistically significant difference in this study.…”
Section: Discussionmentioning
confidence: 99%
“…41 With an increase in hearing threshold, a larger tinnitus severity was observed. 41 The association between degree of hearing loss and the TFI grading found a statistically significant difference in this study. Mazurek et al and Dias et al also concluded that the severity of the discomfort induced by tinnitus is a reflection of the degree of hearing impairment in a tinnitus patient.…”
Section: Discussionmentioning
confidence: 99%
“…Es un método terapéutico que consiste en la inserción y manipulación de agujas en el cuerpo. El tratamiento de los acúfenos mediante este ha sido ampliamente descrito en los libros 28,37,38 . La acupuntura china del cuero cabelludo es una técnica de acupuntura contemporánea que tiene solo 40 años de historia.…”
Section: Acupunturaunclassified